DPP-4 Inhibition and the Path to Clinical Proof - Ahrén, Bo (Frontiers in Endocrinology, 2019)
In the 1990s it was discovered that the enzyme dipeptidyl peptidase-4 (DPP-4) inactivates the incretin hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP). DPP-4 inhibition results in raised levels of the two incretin hormones which in turn result in lowering of circulating glucose through stimulation of insulin secretion and inhibition of glucagon secretion. Since then, several small orally available molecules have been developed with DPP-4 inhibitory action. Early studies in the 1990s showed that the DPP-4 inhibitors improve glycemia in animals. Subsequent clinical studies during the 2000s showed a glucose-lowering action of DPP-4 inhibitors also in human subjects with type 2 diabetes. This action was seen when DPP-4 inhibitors were used both as monotherapy and as add-on to other therapies, i.e., metformin, sulfonylureas, tiazolidinediones or exogenous insulin. The DPP-4 inhibitors were also found to have a low risk of adverse events, including hypoglycemia. Five of the DPP-4 inhibitors (sitagliptin, vildagliptin, alogliptin, saxagliptin and linagliptin) were approved by regulatory authorities and entered the market between 2006 and 2013. DPP-4 inhibitors have thereafter undergone long-term cardiovascular outcome trials, showing non-inferiority for risk of major acute cardiovascular endpoints. Also the risk of other potential adverse events is low in these long-term studies. DPP-4 inhibitors are at present included in guidelines as a glucose-lowering concept both as monotherapy and in combination therapies. This article summarizes the development of the DPP-4 inhibition concept from its early stages in the 1990s. The article underscores that the development has its basis in scientific studies on pathophysiology of type 2 diabetes and the importance of targeting the islet dysfunction, that the development has been made possible through academic science in collaboration with the research-oriented pharmaceutical industry, and that the development of a novel concept takes time and requires focused efforts, persistence and long-term perserverance.